PENGARUH JUMLAH TENAGA PENJUAL TERHADAP PENINGKATAN PENJUALAN POLIS PADA PT. GREAT EASTERN LIFE INDONESIA CABANG PALEMBANG - Nita Novita; Indri Ariyanti (MANAJEMEN INFORMATIKA, 2009)
The aims of this research are 1) to know how big the effect of salesman amount towards the policy sale the increasing at Palembang Branch of PT. Great Eastern Life Indonesia, and 2) to analyze the salesman’s activities in enchancing policy sale to reach sale expected by Palembang Branch of  PT. Great Eastern Life Indonesia.The method used in this research is descriptive. Total of the samples used in this research are 24 salesman, and interview used in collecting data. The simple linear regression used to measure the level of the inter-variable effect.The result show that the salesman amount has an effect toward the amount of 1.02 units towards the sale of the policy. In conducting sale to candidate clients, faced a lot of problems resulting in candidate clients being less sure towards the life insurance. Therefore, the salesman must be able to convince the candidate clients in conducting sale, so that the candidate clients do not hesitate to take the life insurance.